Review Artikel PRODUKSI BIOETANOL BERBAHAN DASAR LIMBAH KULIT KOPI SEBAGAI BAHAN BAKAR ALTERNATIF - Rizanti Fadilah Azzahra; Meilianti (KINETIKA, 2021)
Bioethanol is an innovative solution that is environmentally friendly and able to reduce pollution by agricultural wastes. It has high oxygen content and burns more completely than gasoline. The research was aimed to utilize coffee skin wastes which is known generally as a primary industrial waste for producing a value-added products and to reduce environmental pollution burden as well as to evaluate the potential for bioethanol production at probable optimum conditions using Saccharomyces cerevisiae. Using two different international journals, this article review will compare the methods used from both journals that have the highest bioethanol yield as an alternative biofuel.